2015
DOI: 10.1007/s13277-015-3128-5
|View full text |Cite
|
Sign up to set email alerts
|

High serum microRNA-122 level is independently associated with higher overall survival rate in hepatocellular carcinoma patients

Abstract: Previous studies have shown that some microRNAs (miRs) are intensively involved in the development of hepatocellular carcinoma. We analyzed the prognostic role of serum microRNA (miR-122) levels in hepatocellular carcinoma patients using a retrospective design. MiR-122 levels in 122 hepatocellular carcinoma patients were measured, and Cox regression analysis was performed to analyze the prognostic role of miR-122 in hepatocellular carcinoma, and the hazard ratio (HR) with 95 % confidence interval (95 %CI) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 26 publications
0
41
1
Order By: Relevance
“…miR-125a-5p, miR-128-3p, miR-188-5p, miR-206, miR-212-3p, miR-424-5p and miR-744-5p) were outstandingly correlated with limitless replicative potential and could provide positive prognostic values for HCC3846474852566465697073747687. Four prognostic circulating miRNAs associated with proliferation and limitless replicative potential, including miR-101-3p, miR-122-5p, miR-21-5p and miR-331-3p, were reported up-regulated in HCC patients38566177.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…miR-125a-5p, miR-128-3p, miR-188-5p, miR-206, miR-212-3p, miR-424-5p and miR-744-5p) were outstandingly correlated with limitless replicative potential and could provide positive prognostic values for HCC3846474852566465697073747687. Four prognostic circulating miRNAs associated with proliferation and limitless replicative potential, including miR-101-3p, miR-122-5p, miR-21-5p and miR-331-3p, were reported up-regulated in HCC patients38566177.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, the low expression of miR-125a-5p, miR-128-3p, miR-137, miR-185-5p, miR-188-5p, miR-26a-5p, miR-503-5p and miR-744-5p were detected in HCC tissues compared with their non-tumor livers and were involved in the multi-step processes35363773747576. There were six circulating prognostic biomarker miRNAs reported to be associated with tissue invasion and metastasis, including miR-122-5p, miR-17-5p, miR-182-5p, miR-21-5p, miR-24-3p and miR-331-3p, all of them were up-regulated in the group with low survival rate5661637778. Meanwhile, the serum miR-150-5p was shown highly expressed in HCC patients after surgical operation and then low expressed after tumor relapsed60.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Xu et al [32] and Koberle et al [33] reported that a high serum miR-122 level was associated with longer OS times in patients with HCC. However, the results of these studies are not consistent with our results.…”
Section: Discussionmentioning
confidence: 99%